2023
DOI: 10.3389/fneur.2023.1059789
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation over the posterior parietal cortex improves functional recovery in nonresponsive patients: A crossover, randomized, double-blind, sham-controlled study

Abstract: BackgroundRecent studies have shown that patients with disorders of consciousness (DoC) can benefit from repetitive transcranial magnetic stimulation (rTMS) therapy. The posterior parietal cortex (PPC) is becoming increasingly important in neuroscience research and clinical treatment for DoC as it plays a crucial role in the formation of human consciousness. However, the effect of rTMS on the PPC in improving consciousness recovery remains to be studied.MethodWe conducted a crossover, randomized, double-blind,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…According to information aggregation theory, the posterior parietal cortex (PPC) has been shown to be the largest cortical region associated with consciousness [18]. Xu et al [19] performed 10 Hz rTMS on the left PPC of 24 VS patients and found that it could significantly improve the functional recovery of unresponsive DoC patients. The precuneus is part of the posterior parietal cortex and is located in the BA7 region [20,21].…”
Section: Tms Is At the Stimulation Site Of Patients With Consciousnes...mentioning
confidence: 99%
“…According to information aggregation theory, the posterior parietal cortex (PPC) has been shown to be the largest cortical region associated with consciousness [18]. Xu et al [19] performed 10 Hz rTMS on the left PPC of 24 VS patients and found that it could significantly improve the functional recovery of unresponsive DoC patients. The precuneus is part of the posterior parietal cortex and is located in the BA7 region [20,21].…”
Section: Tms Is At the Stimulation Site Of Patients With Consciousnes...mentioning
confidence: 99%
“…Three levels of bias risk (high, low, and unclear) were applied to grade the included studies. The articles included three high-quality studies with a low-level bias risk [27][28][29], two studies with a high level of bias risk [30,31], and three with a moderate risk of bias [24][25][26]. The risk of bias is shown in Figure 2.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Some studies reported that rTMS over the M1 could affect other brain regions and remedy patients with DoC [23][24][25][26]. A recent study showed that rTMS can be used over the posterior parietal cortex (PPC) to treat patients with DoC; however, the effectiveness requires further studies [27].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is now established that TMS holds an important role in promoting and monitoring functional recovery in severe brain injury (10). In the field of DoC, some studies have investigated rTMS-induced changes on behavior (11) and electrophysiology (12) or both in patients with severe brain damage (12)(13)(14)(15)(16)(17). However, these protocols usually differ in several experimental parameters (e.g., stimulation site, stimulation intensity, number of sessions delivered), making it difficult to draw any conclusion on an effective stimulation protocol at this stage.…”
Section: Therapeutic Options In Docmentioning
confidence: 99%
“…Eventually, two recent open label studies exploring the effect of rTMS over the left parietal cortex found improved behavioral total scores in MCS patients (24) and even in some UWS/VS patients (15). Hence, from these studies, it becomes evident that rTMS is feasible in DoC patients, and that some protocols involving specific target parameters may elicit clinical as well as physiological changes (25), especially in the prefrontal and anterior parietal regions (i.e., DLPFC and angular gyrus, AG).…”
Section: Therapeutic Options In Docmentioning
confidence: 99%